Effect of AlSiFe on the anodizing process of 6063 aluminum. (20th May 2016) - Hu, Lifang; Chen, Daming; Shi, Fangrong; Chen, Shaoping
Abstract : AlSiFe phase can form microscopic galvanic couples that decrease corrosion resistance of 6063 aluminum which may influence the anodizing process. Two samples of 6063 aluminum were prepared. One sample was cut along the extrusion direction of the billet, and the other was cut perpendicular to the extrusion direction. Both samples exhibited the same characteristics, except for the distribution of the second phase AlSiFe. Both samples were subjected to anodizing treatments. Comparison between anodic oxide films was performed. The microstructure of Al substrates and anodic oxide films were examined using a scanning electron microscope, an optical microscope, and a glow discharge optical emission spectrometer. Results indicated that the thicknesses and elemental distributions of the anodic oxide films were almost the same. Moreover, the second phase AlSiFe influenced the anodic oxidation process, resulting in cavities in the anodic oxide film that affected its brightness. Copyright © 2016 John Wiley & Sons, Ltd.